Factors influencing visitors’ use of augmented reality technology in museum guided tours - Ying He; Wenyue Wang (PLoS ONE, 2025)
The emergence of Augmented Reality (AR) technology has provided innovative ideas for museum tourism services, creating a unique tour experience for visitors. However, there is little research known for the user’s behavior of using AR technology in the context of interactive museum guided tour services. This study aimed to explore the factors that drive tourists to use AR guided tours in museums. Based on the Stimuli-Organism-Response framework and the Information System Success Model, this study attempted to construct a model of visitor acceptance of AR guided museum tour for explaining and predicting visitors’ behaviors of AR guided museum tours. Structural equation modeling was used in this study to analyze the data from 324 survey questionnaires. The results showed that individuation and interactivity positively affected satisfaction and perceived enjoyment, authenticity and aesthetics positively affected perceived enjoyment, and perceived enjoyment positively affected satisfaction. In addition, perceived enjoyment and satisfaction positively affected the intention to use AR guided tours. The study has revealed the factors affecting the intention to use AR guided tours, extended the application of the Stimuli-Organism-Response framework and the Information System Success Model, and enriched the theories of museum user behavior. This study can provide valuable references for museum managers, tourism marketers and AR technology developers to enhance the AR tour experience of museum visitors and promote the healthy development of museum tourism.